5x - 3y = 7
First, Add 3y to both sides
5x - 3y + 3y = 7 + 3y
5x = 3y + 7
Then, Divide both sides by 5
=
![(3y + 7)/(5)](https://img.qammunity.org/2022/formulas/mathematics/college/ru8ukjr8dk35u425h9owdcnezvbs1pwxxi.png)
+
(Answer to #1)
-3x - 3x - 5 = 23
First, we will simplify both sides of the equation
-3x + -3x + -5 = 23
Next, We will combine like terms
(-3x + -3x) + (-5) = 23
-6x + -5 = 23
-6x - 5 =23
Then, we will Add 5 to both sides
=
![(28)/(-6)](https://img.qammunity.org/2022/formulas/mathematics/college/pt3j8emtpvg91xckxuv4ndja8zc62t9fb0.png)
x =
(Answer to #2)